2014
DOI: 10.1002/embj.201387329
|View full text |Cite
|
Sign up to set email alerts
|

STAG3‐mediated stabilization of REC8 cohesin complexes promotes chromosome synapsis during meiosis

Abstract: Cohesion between sister chromatids in mitotic and meiotic cells is promoted by a ring-shaped protein structure, the cohesin complex. The cohesin core complex is composed of four subunits, including two structural maintenance of chromosome (SMC) proteins, one a-kleisin protein, and one SA protein. Meiotic cells express both mitotic and meiosis-specific cohesin core subunits, generating cohesin complexes with different subunit composition and possibly separate meiotic functions. Here, we have analyzed the in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
113
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(130 citation statements)
references
References 49 publications
(120 reference statements)
14
113
0
Order By: Relevance
“…In the mouse, although meiotic recombination initiates prior to and independently of synapsis (Mahadevaiah, et al 2001), synapsis is required for recombination sites to repair DSBs via development into meiotic crossovers (de Vries, et al 2005). Although arrest of Prdm9 -mutant spermatocytes is at a more advanced stage than arrest of most single or double mutants for meiosis-specific cohesins (Fukuda, et al 2014; Hopkins, et al 2014; Llano, et al 2014; Llano, et al 2012), Prdm9 -mutant spermatocytes exhibit synapsis defects that are in common with those described for spermatocytes mutant for other proteins playing early roles in the recombination pathway, e.g., SPO11 and DMC1 (Bannister, et al 2007; Baudat, et al 2000; Pittman, et al 1998; Romanienko and Camerini-Otero 2000). These include delayed and/or inefficient repair of DNA DSBs, persistent RAD51 foci and patches of P-H2AFX (this study; Hayashi et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the mouse, although meiotic recombination initiates prior to and independently of synapsis (Mahadevaiah, et al 2001), synapsis is required for recombination sites to repair DSBs via development into meiotic crossovers (de Vries, et al 2005). Although arrest of Prdm9 -mutant spermatocytes is at a more advanced stage than arrest of most single or double mutants for meiosis-specific cohesins (Fukuda, et al 2014; Hopkins, et al 2014; Llano, et al 2014; Llano, et al 2012), Prdm9 -mutant spermatocytes exhibit synapsis defects that are in common with those described for spermatocytes mutant for other proteins playing early roles in the recombination pathway, e.g., SPO11 and DMC1 (Bannister, et al 2007; Baudat, et al 2000; Pittman, et al 1998; Romanienko and Camerini-Otero 2000). These include delayed and/or inefficient repair of DNA DSBs, persistent RAD51 foci and patches of P-H2AFX (this study; Hayashi et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Notably, not all of these proteins co-localize within the same cohesin complexes, i.e., there are several different meiosis-specific cohesin complexes, with separate functions not yet fully understood (Revenkova and Jessberger 2006). Specific single ( Stag3 ) or double ( Rec8 - Rad21l ) cohesin subunit mutants exhibit very early meiotic prophase arrest, in the leptotene stage (Fukuda, et al 2014; Hopkins, et al 2014; Llano, et al 2014; Llano, et al 2012), providing evidence that these proteins are essential for setting up a chromosomal architecture favoring recombination and homology pairing. Interestingly, the temporal setting for establishing the cohesin-mediated meiotic chromosome AEs encompasses the time period when PRDM9 is first detected in male germ-cell nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cohesin complexes are required for accurate recombination and synapsis between homologous chromosomes (Rankin, 2015). Meiosis-specific cohesin components, including SMC1β, two α-kleisins (REC8 and RAD21L) and a stromal antigen protein (STAG3), are important for these additional requirements of cohesins during meiosis (Bannister et al, 2004;Fukuda et al, 2014;Herrán et al, 2011;Hopkins et al, 2014;Llano et al, 2014;Revenkova et al, 2004;Winters et al, 2014;Xu et al, 2005). Mutation of meiosisspecific cohesin components in female mice results in an increased frequency of oocyte aneuploidy and premature ovarian failure The two condensin complexes (I and II) are composed of the SMC2 and SMC4 heterodimers, but their kleisin subunit and pair of HEAT repeat elements are unique (Hirano, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the same group showed that Stag3 mutant spermatocytes exhibit a hypomorphic phenotype during the progression of meiotic prophase, in which the REC8 cohesin level is partly reduced [5]. This evidence prompted the authors to assess the distribution of REC8 at local "axial opening" regions in the Stag3 mutant.…”
mentioning
confidence: 99%